Business Development Strategy of Family Medicinal Plants from the Economic Side: A Case Study of Seuriget Village of West Langsa Sub-District - Syardiansah Syardiansah (Proceedings of AICS - Social Sciences, 2018)
This research was conducted with the aim of identifying, collecting, processing and analyzing data about strength factors, weakness, opportunity, threats in developing the family medicinal plant business from the economic and business development strategy of family medicinal plants from the economic side of the research area. The population in this study is the people who grow the family medicinal plants in the yard of the house in the village of Seuriget District Langsa Barat. The sample is the entire population of 35 families. The data sources in this study was primary and secondary data. Data analysis method used was descriptive analysis with SWOT analysis. From the research result, it was that the strength in the development of family medicine plant business from the economic side was taken an organic medicine. The weakness in the development of family medicinal plant business from the economic side is the price is still low from the economic and plant side which was used as slow drug result. Opportunities in the development of family medicinal plant business from the economic side are always needed by the community, in addition, to being used as medicine and apply the pattern of life back to nature with organic materials. Threats to the development of family medicinal plant business from the economic side are fewer enthusiasts who use family medicinal plants as the alternative to drugs and prefer to use chemical-based drugs. The development strategy of the family’s medicinal plant business was focused on increasing the community’s interest in the needs of family medicinal plants that can be taken as an organic medicine besides raw materials for cooking and can be processed into food or other forms of more economic value.Keywords: strengths, weaknesses, opportunities, threats.